2010
DOI: 10.14195/2183-203x_32_2
|View full text |Cite
|
Sign up to set email alerts
|

Mind the gap: education inequality at the regional level in Portugal, 1986-2005

Abstract: A navegação consulta e descarregamento dos títulos inseridos nas Bibliotecas Digitais UC Digitalis, UC Pombalina e UC Impactum, pressupõem a aceitação plena e sem reservas dos Termos e Condições de Uso destas Bibliotecas Digitais, disponíveis em https://digitalis.uc.pt/pt-pt/termos.Conforme exposto nos referidos Termos e Condições de Uso, o descarregamento de títulos de acesso restrito requer uma licença válida de autorização devendo o utilizador aceder ao(s) documento(s) a partir de um endereço de IP da insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 32 publications
1
10
1
Order By: Relevance
“…Given the importance of the distribution of human capital for economic growth and the distribution of income, Fidalgo et al (2010) compute the distribution of average years of schooling of the working population for Portugal using data from QP for the years 1986, 1996 and 2005. The overall conclusion, based on the behaviour of different measures, is that Portugal recorded a decrease in education inequality. The authors also find evidence of a Kuznets inverted U relationship between the level of education and education inequality, based on regional data.…”
Section: Human Capital and Earnings Inequality: An Overviewmentioning
confidence: 99%
“…Given the importance of the distribution of human capital for economic growth and the distribution of income, Fidalgo et al (2010) compute the distribution of average years of schooling of the working population for Portugal using data from QP for the years 1986, 1996 and 2005. The overall conclusion, based on the behaviour of different measures, is that Portugal recorded a decrease in education inequality. The authors also find evidence of a Kuznets inverted U relationship between the level of education and education inequality, based on regional data.…”
Section: Human Capital and Earnings Inequality: An Overviewmentioning
confidence: 99%
“…In education, (Ram 1990;Shukla & Mishra, 2019;Thomas et al 2001) examined the correlation pattern inverted U-shaped between education expansion and schooling of standard deviation. The education Gini index as a measure of education inequality was evaluated by (Fidalgo et al 2010;Hojo 2009;Shukla & Mishra 2019;Thomas et al 2001), and student attainment was examined (Guarini et al 2018). These results of these studies were able to demonstrate that the pattern of correlation between education and the standard deviation of schooling could develop the inverted U-shaped relationship pattern.…”
Section: Introductionmentioning
confidence: 99%
“…They are interested in checking the impact of openness into regional growth, which found that was important, especially for the litoral regions. Other works were focused in other drivers as European funds in Soukiazis and Antunes (2006), tourism in Soukiazis and Proença (2008) and education in and Fidalgo et al (2010). Vieira et al (2006) found that differences in regional wages were related to education.…”
Section: Introductionmentioning
confidence: 99%
“…(2006), Soukiazis and Antunes (2006, 2011), Soukiazis and Proença (2008), Fidalgo et al . (2010) and Pereira and Galego (2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation